2014
DOI: 10.2147/ijn.s71700
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Mycobacterium tuberculosis based on H37Rv binding peptides using surface functionalized magnetic microspheres coupled with quantum dots – a nano detection method for Mycobacterium tuberculosis

Abstract: Despite suffering from the major disadvantage of low sensitivity, microscopy of direct smear with the Ziehl–Neelsen stain is still broadly used for detection of acid-fast bacilli and diagnosis of tuberculosis. Here, we present a unique detection method of Mycobacterium tuberculosis (MTB) using surface functionalized magnetic microspheres (MMSs) coupled with quantum dots (QDs), conjugated with various antibodies and phage display-derived peptides. The principle is based upon the conformat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(29 citation statements)
references
References 29 publications
0
29
0
Order By: Relevance
“…tuberculosis associated with magnetic beads has been employed, including sandwich detection using functionalized magnetic microspheres and quantum dots conjugated with specific antibodies (Yang et al . ) and direct detection using TB beads coated with polymeric ligand and auramine‐O fluorochrome staining (Wilson et al . ; Albert et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…tuberculosis associated with magnetic beads has been employed, including sandwich detection using functionalized magnetic microspheres and quantum dots conjugated with specific antibodies (Yang et al . ) and direct detection using TB beads coated with polymeric ligand and auramine‐O fluorochrome staining (Wilson et al . ; Albert et al .…”
Section: Discussionmentioning
confidence: 99%
“…The detection of Myco. tuberculosis associated with magnetic beads has been employed, including sandwich detection using functionalized magnetic microspheres and quantum dots conjugated with specific antibodies (Yang et al 2015) and direct detection using TB beads coated with polymeric ligand and auramine-O fluorochrome staining (Wilson et al 2010;Albert et al 2011). Herein, anti-Ag85B mAb clone AM85B-8 specific to mycobacterial Ag85B protein coupled with magnetic beads were facilitated for selective separation of Mycobacterium spp.…”
Section: Ifmentioning
confidence: 99%
“…Due to these advantages, SPR has emerged as a powerful optical tool, which can provide valuable data in the analysis of biomedical and chemical analyses. The SPR-based CFP-10 antigen detection system was developed in clinical samples by Yang et al (2014), which showed reputable usefulness in TB diagnostics (Hsieh et al 2012;Yang et al 2014). Zhu et al (2017) developed AuNPs modified indium tin oxide (ITO) electrode for the direct detection of M. tuberculosis using genomic DNA (gDNA) isolated directly from clinical samples.…”
Section: Gold Nanoparticle (Aunps)-based Diagnostics For Tbmentioning
confidence: 99%
“…[96][97][98] One particularly interesting example of the utility of QDs also took advantage of the separation/concentrating characteristics of MNPs to develop a method to detect Mycobacterium tuberculosis (Mtb) biomarkers in the sputum of infected patients. [99] The intent was to take advantage of the optical strengths of QDs -high quantum yields and low fluorescent NPs offer many sought-after advantages in expanding the fluorescent toolbox, such as robustness, versatility, and synthetic simplicity. However, like QDs, there are still questions regarding the toxicity of these NPs and the reagents used in their synthesis.…”
Section: Emission-based Detectionmentioning
confidence: 99%